THE INFLUENCE OF AUDITOR COMPETENCE AND ETHICS ON AUDIT QUALITY OF AN EMPIRICAL STUDY IN THE OFFICE PUBLIC ACCOUNTANT IN MEDAN CITY - Putri Br Purba; Dwi Saraswati (Yayasan Multidimensi Kreatif, 2025)
The problem in this study is that there are auditors who are less competent in knowledge, skills, and experience, thus affecting the quality of audits. There are violations of auditor ethics, such as collusion or bribery, that interfere with independence and objectivity. Non-compliance with audit standards, due to client pressure or lack of understanding. There is a low quality of audits, which lowers public confidence in financial statements. There is a lack of understanding of ethics and competence, which is an important basis in the implementation of audits. This study aims to determine the influence of Auditor Competence and Erika on Audit Quality, both directly and simultaneously. This study uses a quantitative approach with associative nature and data collection techniques using questionnaires. The results of the study show that there is an influence of Competency on the Quality of Audit of the Empirical Study of the Medan Public Accounting Firm. There is an influence of Auditor Ethics on the Quality of Audit of an Empirical Study of Medan Public Accounting Firms. There is a simultaneous influence of Auditor Competence and Ethics on the Quality of Audit Empirical Studies of Medan Public Accounting Firms.